Role and translational implication of galectins in arthritis pathophysiology and treatment: A systematic literature review. Issue 2 (24th August 2018) - Salamanna, Francesca; Veronesi, Francesca; Frizziero, Antonio; Fini, Milena
Abstract : Galectins are members of the animal lectin family that bind to the β‐galactoside‐containing carbohydrate moieties of glycoconjugates. They seem to have an important role in the pathophysiology of several diseases, including arthritis. Osteoarthritis (OA) and rheumatoid arthritis (RA) are chronic conditions with few or no available therapies. In this context, galectins could provide a novel opportunity, but the precise role and mechanism of their involvement in arthritis are still not fully understood. This descriptive systematic literature review summarizes in vitro, in vivo, and clinical studies that analyzed and examined the role and mechanism of action of galectins in arthritis to highlight and clarify their possible translation implication. This review yielded promising evidence that individual galectins, in particular galectin‐1, ‐3, and ‐9, could play positive or negative roles in the pathogenesis of arthritis, especially in RA and OA. It also emphasized the cell‐dependent role of these galectins. This is particularly true for galectin‐1, which was shown to have a protective anti‐inflammatory role in RA, while it seemed to be associated with cartilage degeneration in OA. In summary, this review underlined that manipulation of certain galectins can suppress or aggravate disease symptoms in arthritis animal models, demonstrating the therapeutic potential of galectins for the treatment of RA and OA. Nevertheless, despite the fact that galectin therapy and therapies acting on galectin expression seem to be an interesting and important opportunity for research, we highlighted that further investigation is necessary to carefully evaluate their potential clinical implications in arthritis. Abstract : Galectins are members of the animal lectin family that bind to the β‐galactoside‐containing carbohydrate moieties of glycoconjugates. This descriptive systematic literature review summarizes in vitro, in vivo, and clinical studies that analyzed and examined the role and mechanism of action of galectins in arthritis to highlight and clarify their possible translation implication. Manipulation of certain galectins can suppress or aggravate disease symptoms in arthritis animal models, demonstrating the therapeutic potential of galectins for the treatment of rheumatoid arthritis and osteoarthritis.